Min Niẓām al-Qaḍā al-Munfarid ila Niẓām Majlis al-Quḍāt: Dirāsat fī Taḥwīl Usus al- Qaḍā bī Indūnīsiyā - M. Arskal Salim (Studia Islamika, 1999)
"The translation of Islam" to quote M.B. Hooker-constitutes one important dimension in the Islamization process: it is the means through which Islamic principles come into the local context. In Indonesia, the translation of Islam can be seen, among other things, in the legal institution, The "solitary judge" (hakim tunggal) as it is know in early Islan is transformed into the "Judicial assembly" (majlis hakim). In the first system, the solitary judge, kadi is the only judge responsible for the implementation of Islamic law, while in the second system, the judicial assembly, legal decisions are made collectively and involvee at least three judges.DOI: 10.15408/sdi.v6i2.733